2020
DOI: 10.14744/nci.2020.04764
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of static and electric fields on bone healing process: an experimental tibial fracture model study in wistar-albino male rats

Abstract: OBJECTIVE: In this experimental study, we aimed to investigate whether 0 Hz-Static and 50 Hz-Electric fields have an effect on bone healing. METHODS: In this study, 45 male Wistar-Albino rats were equally and randomly separated into three groups as follows: a 0 Hz-Static electric field (SEF), a 50-Hz low-frequency electric field (LFEF) and a control group. A manual fracture was performed in the left tibia diaphysis of all rats, and fractures were fixed using circular pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
0
1
Order By: Relevance
“…On the other hand, recent research has shown that the bioelectric effect was able to completely eradicate the bacterial biofilm from saliva-contaminated titanium surfaces within 5 min of exposure without damaging mammalian tissues ( Al-Hashedi et al, 2016 ). In another study, researchers reported that the exposure to 0-hz static and 50-hz electric field may affect bone healing tissue of tibial fractures in rats; however, their results were not significant, and the exposure to the bioelectric effect in this study was of several weeks ( Aslan et al, 2020 ). Therefore, a relatively short exposure to a low electric current is not expected to cause significant effects on the surrounding bone tissues.…”
Section: Discussioncontrasting
confidence: 54%
“…On the other hand, recent research has shown that the bioelectric effect was able to completely eradicate the bacterial biofilm from saliva-contaminated titanium surfaces within 5 min of exposure without damaging mammalian tissues ( Al-Hashedi et al, 2016 ). In another study, researchers reported that the exposure to 0-hz static and 50-hz electric field may affect bone healing tissue of tibial fractures in rats; however, their results were not significant, and the exposure to the bioelectric effect in this study was of several weeks ( Aslan et al, 2020 ). Therefore, a relatively short exposure to a low electric current is not expected to cause significant effects on the surrounding bone tissues.…”
Section: Discussioncontrasting
confidence: 54%